SEED VIABILITY OF SOME LOCAL RICE VARITIES OF SOUTH KALIMANTAN TIDAL SWAMP THAT WERE IRRADIATED BY GAMMA RAY - Wahdah, Raihani; Zulhidiani, Rahmi (Agroscientiae, 2014)
The increasing of base population variability can be done by induction of physical mutation by gamma ray.Â The objective of this research was to know responses of seed viability of some local rice varieties of SouthÂ Kalimantan tidal swamp that were irradiate d by gamma ray. The experiment was carried out in PlantÂ Physiology Laboratory, Agriculture Faculty, Lambung Mangkurat University based on Factorial RandomizedÂ Block Design, namely 7 (varietas) x 4 (doses) x 2 (replication). The observation were done on seed germination, seed growth uniformity, plumula lenght of strong normal seedling, root lenght of strong normalÂ seedling, dry weight of normal seedling, and speed of seed germination. Data were analized by F -tes (Anova). If interaction or single factor were significant, so continued by LSD (Least Significant Difference) werenât equal. Seed germination, seed growth uniformity, and speed of seed ger mination of Siam Unus Kuning Variety (7) wasnât affected by dose of irradiation of gamma ray. The effect of gamma ray on someÂ doses on each varieties have decreased seed viability. The worst performance for all variable were in highest dose, namely 30 kradÂ